Diversity and Transcriptional Levels of RuBisCO Form II of Sulfur-Oxidizing γ-Proteobacteria in Coastal-Upwelling Waters with Seasonal Anoxia - Léniz, Bárbara; Murillo, Alejandro A.; Ramírez-Flandes, Salvador; Ulloa, Osvaldo (Frontiers in Marine Science, 2017)
Seasonal wind-driven upwelling, high primary production in surface waters, and oxygen deficiency in subsurface waters characterize the coastal ecosystem of the subtropical eastern South Pacific (ESP), and shape the nature and dynamics of the microbial community structure and function. We investigated the diversity, abundance, and transcriptional levels of the gene encoding the large subunit form II of the RuBisCO enzyme (cbbM) in the pelagic microbial community at a continental-shelf site off central Chile over two years. We focused on cbbM genes affiliated with the sulfur-oxidizing -proteobacteria cluster, whose members are known to dominate in oxygen-deficient marine environments and are highly abundant in the study area. Phylogenetic analysis of cbbM sequences suggests the presence of a novel group of chemolithoautotrophs, closely related to the SUP05/ARCTIC96BD-19 clade. Through (RT)-qPCR, we studied the cbbM gene abundance and transcript dynamics over an annual cycle, finding a significantly higher number of cbbM copies per unit volume in months of active upwelling and at depths in which oxygen was scarce or absent. The same temporal pattern was observed at the transcriptional level. We also analyzed the relative expression of key genes for carbon, nitrogen and sulfur cycling in six metatranscriptomic datasets, for two characteristic periods within the annual cycle: the anoxic upwelling and the suboxic downwelling. Our results indicate that coastal waters of the subtropical ESP contain transcriptionally active populations of carbon fixing pelagic bacteria, whose dynamics is controlled, in large part, by fluctuations in oxygen levels. They also suggest that chemolithoautotrophic processes coupled to the sulfur and nitrogen cycles become increasingly important for the carbon economy of marine coastal waters as oxygen concentrations decline.